Early myocardial and skeletal muscle interstitial remodelling in systemic sclerosis: insights from extracellular volume quantification using cardiovascular magnetic resonance. (4th September 2014) - Barison, Andrea; Gargani, Luna; De Marchi, Daniele; Aquaro, Giovanni Donato; Guiducci, Serena; Picano, Eugenio; Cerinic, Marco Matucci; Pingitore, Alessandro
Abstract: Aims: Systemic sclerosis (SSc) may induce cardiac fibrosis and systo-diastolic dysfunction. Cardiovascular magnetic resonance (CMR) can detect replacement myocardial fibrosis with late gadolinium enhancement (LGE) and interstitial myocardial fibrosis with T1 mapping techniques. The aim of the study was to detect subclinical cardiac involvement with CMR in paucisymptomatic SSc patients with no previous history of myocardial disease, comparing it with skeletal muscle remodelling. Methods and results: Thirty consecutive SSc patients (mean age: 51 ± 12 years, all women) and 10 healthy controls (mean age: 48 ± 15 years, all women) underwent clinical, biohumoral assessment, and CMR. Extracellular volume fraction (ECV) was calculated from pre- and post-contrast T1 values in the myocardium and skeletal muscle. Seventeen patients (57%) were asymptomatic, 13 (43%) paucisymptomatic (effort dyspnoea). All patients had normal biventricular volumes and systolic function, while LGE was present in seven patients (23%). Myocardial ECV was significantly increased in patients with SSc (30 ± 4%) than controls (28 ± 4%, P = 0.03), as was skeletal muscle ECV (23 ± 6% vs. 18 ± 4%, P < 0.01). Myocardial ECV did not differ between patients with and without LGE ( P = NS) and showed no significant correlations with clinical data, biventricular volumes, systolic, or diastolic function. Overall, myocardial ECV showed a significant correlation with skeletal muscle ECV ( R = 0.58, P < 0.001). Conclusion: SSc is associated not only with myocardial replacement fibrosis, as detected by LGE, but also with interstitial remodelling of the myocardium and skeletal muscles, as detected by an increased ECV also in patients with normal biventricular function, with potential diagnostic, prognostic, and therapeutic clinical implications.